Study use of Antiepileptic Drugs in Pediatric Ward at GMERS Hospital, Gandhinagar, India - Christian, Princy; Patel, Janki; Deshapande, Shrikalp; Shah, Seema (Indian Journal of Pharmacy Practice)
Introduction: Epilepsy, a common neurological disorder characterised by a transient paroxysm of neuronal discharge and the condition seizure disorder is reported majorly among pediatric population. Around 4-10 % of children suffer atleast 1 seizure in their first 16 years of life. It includes febrile convulsion (typical or atypical), epilepsy or any neurological disorder. Anti-epileptic drugs are the primary therapeutic measure to control seizure and manage epilepsy. To determine rationality of therapy, it is necessary to have knowledge on how drugs are prescribed and used to treat a particular disease or a group of diseases in the clinical setting and so due to paucity of data on anti-epleptic drugs usage amongst pediatric population in India, drug use study was conducted. Objectives: The study aims to determine the utilization pattern of anti-epleptic drugs in in-patient admission in pediatric wards of GMERS Hospital, Gandhinagar. Materials and Methods: The study was a prospective observational cross sectional study which was conducted for a period of 4 months. Data of 132 pediatric patients prescribed with anti-epleptic drugs by were enrolled and the resource used to collect data included subjects case notes which was recorded on a pre-structured data collection form. Utilization pattern of anti-epleptic drugs was assessed based on socio-demographic variables, clinical profile, therapy and newer and conventional drugs. Results: Total 1687 patients were admitted, out of which 132 were prescribed with anti-epleptic drugs. Majority of anti-epleptic drugs were prescribed in 2-12 years age group (59%) and in boys (56%). Febrile convulsion (40%) being the most commonly diagnosed condition followed by epilepsy (29%) amongst the study population. Midazolam were administered to 113 patients (41%), being the most frequently prescribed benzodiazepine the frequently used dual therapy was midazolam+phenytoin followed by midazolam+clobazam. The most used triple therapy was midazolam+phenytoin+sodium valproate. Conclusion: Phenytoin was the most used anti-epleptic drugs and midazolam was the most used benzodiazepens Midazolam monotherapy was used as a first line drug for management of seizure attack. If seizure was not controlled with midazolam then phenytoin was added. Conventional anti-epleptic drugs were used more as compared to newer AEDs.
Keywords: Epilepsy; Drug utilization; Seizures; Anti-epileptics; Paediatrics.